Effects of moderate-to-heavy sled training using different magnitudes of velocity loss in professional soccer players - Grazioli, R.; Loturco, I.; Lopez, P.; Setuain, I.; Goulart, J.; Veeck, F.; Inácio, M.; Izquierdo, M.; Pinto, R. S.; Cadore, E. L. (The Journal of Strength and Conditioning Research, 2023)
This study investigated the effects of a 11-week moderate-to-heavy sled training intervention with different magnitudes of velocity loss on sprint and jump performance, mechanical muscle function, and body composition in professional soccer players. Seventeen players (age 25.8 ± 4.3 years; height 180.0 ± 8.6 cm; mass 77.7 ± 9.7 kg) were randomly allocated into 2 groups, based on different magnitudes of velocity loss: 10% of velocity decrease (G10, n = 8) and 20% of velocity decrease (G20, n = 9). The velocity-based sled training consisted of 20-m resisted sprints with a progressive loading increase from 45 to 65% of body-mass throughout the intervention. Pre-intervention and postintervention sprint and jump performance, hamstring and quadriceps peak torque and isometric rate of torque development, and lower-limb lean mass measured by dual X-ray absorptiometry were assessed and compared. Two-way repeated measures analysis of variance revealed a significant time-effect for decreases in 10- and 20-m sprint times (p = 0.018 and p = 0.033, respectively), but without a time-group interaction. The G10 showed greater beneficial effects than G20 for both 10-m (-5.5 ± 3.3%, magnitude-based inference [MBI]: possibly vs. -1.7 ± 5.9%, MBI: possibly trivial) and 20-m (-2.5 ± 2.1%, MBI: possibly vs. -1.4 ± 3.7%, MBI: likely trivial) sprint times. Moreover, there was a significant time effect for countermovement jump height and quadriceps isometric peak torque, which decreased significantly after training (p = 0.019 and p = 0.010, respectively), with no within-group effect of time vs. group interaction for these respective outcomes. The novel velocity-based sled model proposed here, especially under lower magnitudes of velocity loss, was able to significantly improve linear sprint performance in professional soccer players.